Pelatihan Menggunakan Buli Buli Panas untuk Mengurangi Nyeri Haid pada Remaja di Desa Mulyorejo Kecamatan Sunggal Kabupaten Deli Serdang - Listrianah, Listrianah; Siswati, Sri; Indarsati, Dina; Juliandi, Juliandi (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2021)
Dysmenorrhea is an imbalance of the hormone progesterone in the blood, causing pain to arise, psychological factors also play a role in the occurrence of dysmenorrhea in some women. Women have experienced dysmenorrhea as much as 90%. In Indonesia, the prevalence of dysmenorrhea is around 55% among productive ages. This problem affects at least 50% of women during their reproductive years and 60-85% in their teens, which results in many absenteeism at school and work. In general, 50-60% of women require analgesic drugs. The problem with partners in the community in Muliorejo, Sunggal District, Deli Serdang Regency, is that the knowledge of adolescents in Muliorejo village regarding dysmenorrhea is still low, many adolescents who experience ysmenorrheado not know about efforts to reduce pain from non-pharmacological aspects. The targets of this community service activity are teenagers aged 12-22 years, totaling 40 who are in a state of signs of dysmenorrhea symptoms in Muliorejo Village, Sunggal District, Deli Serdang Regency. The results of this community service are 40 respondents who have been trained in giving hot bladders, there are 35 respondents who have good knowledge about how to deal with dysmenorrhea with non-pharmacological treatment and 5 respondents have sufficient knowledge. The conclusion of this activity is that the knowledge of adolescents in Muliorejo Village about dysmenorrhea in Adolescents is getting better, Youth in Muliorejo Village have been trained about giving hot bladders to reduce dysmenorrhea, By training teenagers about giving hot bladders to reduce dysmenorrhea they can do it independently when dealing with dysmenorrhea. Suggestions for the youth of Muliorejo Village to often reading the leaflets that are shared or information from health services about dysmenorrhea, often re-demonstrating the provision of hot bladders to reduce dysmenorrhea, coordinating with cadres about the technique of giving hot bladders.Keywords: hot bladder, dysmenorrhea